Analisis Konsep Sabar Perspektif Al-Ghazali dalam Karakter Sri Ningsih pada Novel tentang Kamu Karya Tere Liye - Sariah Sariah; Afif Anshori; Nesia Mu’asyara (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This study aims to analyze the concept of patience (sabr) from Imam Al-Ghazali’s perspective and its implementation in the character of Sri Ningsih in the novel Tentang Kamu by Tere Liye. According to Al-Ghazali, patience is divided into three main aspects: patience in facing misfortune, patience in avoiding sinful acts, and patience in maintaining obedience. These aspects are fully integrated in Sri Ningsih’s life journey, who endures various hardships, slander, imprisonment, and struggles abroad. This research applies a qualitative method using literature review and content analysis. The findings reveal that Sri Ningsih consistently practices the values of patience, making her a role model for mental resilience, honesty, and self-control in the midst of modern life’s challenges. This study is expected to contribute to strengthening tasawuf akhlaqi values through literary works.